IT and good governance - Kapur, Jagdish C. (2000)
With a backdrop on prevelance of cynicism on possibility of reforming the process of administration itself on account of persistent failures in reform efforts, the author focuses on IT's role in realising good governance. Prescribing an agenda, with its essential pre-requisite, for the purpose, he relates IT applications to diversified specific areas of governance to impart an element of realism to the discussion. He, however, underscores certain conditionalities, which, according to him, must be fulfilled before visualising success in the mission of IT applications, and concludes by giving the characteristic features of IT-enabled governance. - Reproduced
Keywords: Good governance; Public administration; E commerce; E governance; Information technology